Advanced voice function assessment: Editorial introduction to this special issue. (April 2015) - Barney, Anna; Kob, Malte
Abstract: ICT COST Action 2103 was an EU-funded collaborative network of speech processing engineers, laryngologists, and phoniatricians that started on 19 December 2006 and ended on 18 June 2011. The main objectives were to improve the clinical assessment of voice using new technologies; to encourage clinicians and technologists to work closely together to understand the needs and limitations of each other's fields and, in parallel, to acquire new data with a view to elaborating better voice production models. The papers in this special issue represent some of the outcomes of that partnership. This editorial introduces the background and context for COST Action 2103 and each of the papers. In conclusion we discuss the impact of the Action and what aspects of it may have a lasting effect on practice.